Applicability of spatial planning system package for the LADM Turkey country profile - Yilmaz, Okan; Alkan, Mehmet (WILEY, 2024)
Spatial planning plays a crucial role in shaping the future of urban development and land administration. While land registration information is necessary for spatial planning processes, it is also probable that changes in land registration data occur in line with spatial plan decisions. Development of the Land Administration Domain Model (LADM) Edition II It also aimed to extend its existing conceptual model with spatial plan data, considering the close connection between the two systems. The study aims to design a conceptual model for Turkey's spatial planning system within the LADM Turkey country profile context. This article researches the capability of the proposed conceptual model for representing spatial planning data with instance-level diagrams and the implementation opportunities of a technical model. To demonstrate the functionality of the proposed model, the zoning status certificate, which contains spatial plan and land registration data and is provided to inform about the legal conditions before development, is chosen as the mission. The results show that the LADM Turkey country profile extended with spatial planning system data can represent spatial plan data and be implemented in a technical model to support land administration applications.
Keywords: ADMINISTRATION DOMAIN MODEL; LAND; IMPLEMENTATION; DESIGN; Geography